SONG AS THE FIRST FORM OF MUSIC ART (ART AND CULTURE BULLETIN, 2026)
It is emphasized that the art of singing is the foundation of music when a person feels the powerful power of a beautiful song or melody, even if they cannot read or write
Keywords: singer; sound power; romance; range; register; intonation; diaphragm